A gain enhanced linear polarization switchable array antenna with switching diodes. Issue 10 (23rd June 2022) - Hossain, Md. Azad; Murshed, Abu Hena; Rahman, Muhammad Asad; Nishiyama, Eisuke; Toyoda, Ichihiko
Abstract: In this article, an array antenna possessing linear polarization switchable ability with enhanced gain is proposed by employing 4‐patch elements in square shape. The 4‐elements were arranged on the upper plane of the antenna where edge to edge distances were set to be 0.8 λ of its operating frequency. The radio frequency signal was fed to energize the patch elements by means of a feed circuit which was realized by the both‐sided microwave integrated circuit technology. In addition, polarization switching is done by simply utilizing diode at the corner of the elements as switching elements to perform beam tilting. The incorporation of extra Magic‐T circuit to feed dc bias signal to the diodes helps to achieve improved isolation between feeding signal and the isolation was found to be less than −25 dB. The array antenna was designed to operate at 10.2 GHz and the dimensions of the patch elements was chosen to be 9.4 × 9.4 mm 2 . A Teflon glass fiber of 0.8 mm was used as the dielectric substrate having dielectric constant 2.15 while simulation. Later the proposed antenna was fabricated performance is validated experimentally. The measured S11 was found to be less than −15 dB at operating frequency with a neat measured gain of 13.1 dBi, higher compared with 7.1 dBi gain of single antenna, with minimized sidelobe levels of less than −10 dB. The crosspolarization for the radiation pattern was found better than 20 dB which was an excellent result. The measured polarization angle was found to be −44.24° and +46.20° for negative and positive bias respectively at operating frequency with a neat efficiency of more than 80% in its operating bandwidth. The proposed array antenna is a suitable candidate for the application in polarimetric Radar, X‐band radar, and polarization diversity applications for being lightweight in structure which was made possible using this novel technology. The antenna simulation is done by the advanced design system and the optimized along with experimental data are discussed in this article.